2002
DOI: 10.1007/s00264-001-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of spinopelvic parameters in patients with lumbar disc lesions

Abstract: Using a special software program we measured spinopelvic parameters on digitised radiographs of the entire spine and the pelvis of 50 patients with lumbar disc herniation and compared these with the same measurements on 30 healthy subjects. In the disc hernia group the patients had a relatively straight spine in the sagittal plane. The sacrum was more vertical, and the value of the lumbar lordosis was lower, as was the amplitude of the spinal curvatures, when compared with those of the healthy group. This resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 6 publications
2
25
1
Order By: Relevance
“…Summating both sacral sharpness and lumbar lordosis as global lumbosacral angle, a statistically significant association to lumbar degenerative disc pathologies was found in our series. Furthermore, in subject group the body of S1 exhibited less funneling in shape, which is comparable with other investigations focusing on more vertical sacrum in patients with lumbosacral discopathy [ 7 , 10 ]. Nevertheless, S1 angle was not significantly different between the subjects and the controls; besides, the difference of lumbar lordosis between the two groups was not significant in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Summating both sacral sharpness and lumbar lordosis as global lumbosacral angle, a statistically significant association to lumbar degenerative disc pathologies was found in our series. Furthermore, in subject group the body of S1 exhibited less funneling in shape, which is comparable with other investigations focusing on more vertical sacrum in patients with lumbosacral discopathy [ 7 , 10 ]. Nevertheless, S1 angle was not significantly different between the subjects and the controls; besides, the difference of lumbar lordosis between the two groups was not significant in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to numerous discussions regarding the relationship between lordosis and LBP, only a few controlled studies have assessed the correlation of lumbar sagittal alignment to degenerative disc disease (DDD) or disc herniation (DH) [ 7 ]. Spino-pelvic morphology and sacral alignment received even less attention in this regard [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high levels of LL and SA, especially via passive means, may contribute to tissue strain and injury (Hamill et al, 1995). Clinical evidence suggests a link between LL and spinal pathology (Berlemann et al, 1999;Umehara et al, 2000;Kumar et al, 2001;Rajnics et al, 2002;Labelle et al, 2005;Barrey et al, 2007;Chen and Wei, 2009). Furthermore, the results of this study show that increased SA is associated with increased dynamic lumbar compliance, possibly suggesting higher amounts of strain in back tissues.…”
Section: Discussionmentioning
confidence: 56%
“…Many studies have reported spinopelvic parameters in normal and low back pain populations5,7,9,16,17,19). PI is an important anatomic parameter that describes the anatomic configuration of the pelvis and greatly influences the sagittal configuration of the spine4,10,11).…”
Section: Discussionmentioning
confidence: 99%